Regesten Kaiser Friedrichs III. (1440−1493), Heft 34 Die Urkunden und Briefe des Österreichischen Staatsarchivs in Wien, Abt. Haus-, Hof und Staatsarchiv: Allgemeine Urkundenreihe, Familienurkunden und Abschriftensammlungen (1476−1479) - Holzner-Tobisch, Kornelia (2020)
The volume provides 332 abstracts of charters issued by Emperor Frederick III (1440-1493) between 1476 and 1479, which are preserved in the former Habsburg House and State Archives (Haus-, Hof- und Staatsarchiv) in Vienna. During this period, the course for the future was set: in the West, the war of succession in the Duchy of Burgundy began, in the East, persistent tensions with Hungary resulted in open war. Thus, the most significant documents of the volume are those referring to the peace negotiations with the King of Hungary, Matthias Corvinus (1477), and the complex of charters related to the investiture of Frederick´s son Maximilian with Burgundy (1478), whereas a main focus is on the administration of the hereditary Habsburg territories, which are marked by an increase in written records and also charters issued by the imperial chancellery.